Using learning models problem based learning to improve students' mathematical critical thinking skills - zulkarnain, Mhd azmi; Syaiful, Syaiful; Suratno, Suratno (Desimal: Jurnal Matematika, 2023)
The purpose of this study is to describe how the Problem Based Learning (PBL) learning model improves students' mathematical critical thinking skills on Pythagorean theorem material. A quasi-experimental design was used with a non-equivalent pre-test and post-test control group design. The researchers collected data on critical thinking skills using a descriptive test instrument. The data were analyzed using ANOVA with a significance level of 0.05. The result of data analysis shows that the critical thinking skills of students who learn with the PBL model are better compared to those of students who learn conventionally, and learning to use PBL has similarities to the effectiveness of improving students' critical thinking skills in low, medium, and high level subgroups.